Question

# Use the fact that the inverse of [ 1 -1 2 0 1 0 0 -1...  Use the fact that the inverse of [ 1 -1 2 0 1 0 0 -1 -1 ] 0 1 -1 1 | 1 4 1 3 - 1 1 -1 2 1 2 1 2 0 - 1 1 - 2 10 -1 0 -1 to solve the given system of equations. W - x + 2y = -2 x - y + z = 4 x - y + 2z = -4 -x + y - 2z = -1 -W +
DOOD

We need at least 10 more requests to produce the answer.

0 / 10 have requested this problem solution

The more requests, the faster the answer.

All students who have requested the answer will be notified once they are available.

#### Earn Coins

Coins can be redeemed for fabulous gifts.

Similar Homework Help Questions
• ### QUESTION 2 . 14 POINTS Given the following system of equations, use the inverse of a... QUESTION 2 . 14 POINTS Given the following system of equations, use the inverse of a matrix to solve the system. Give your answer as an ordered tuple. If there is no solution, enter Ø. -*+y+2z=1 33 - y - 42 - 7 4.x - 2y - 4x = -2 Provide your answer below: FEEDBACK

• ### 4. Solve the following system of linear equations using the inverse matrix method. 1 y =... 4. Solve the following system of linear equations using the inverse matrix method. 1 y = 1 2 , 3 2 -r- 1 5 4 a) x+y +z= 6 x-y-3z=-8 x+y- 2z=-6 b) Solve the following system of linear equations using Cramer's Rule. 5. 2 1 -X- 3 2 1 3 X+-y-1 5 4 y = 1 a) x+y+z= 6 x-y-3z=-8 x+y- 2z = -6 b) 4. Solve the following system of linear equations using the inverse matrix method. 1...

• ### 0 7. Let A= 71 -2 1 2 -1 -1 (1 2 2 , B= 1... 0 7. Let A= 71 -2 1 2 -1 -1 (1 2 2 , B= 1 -2 1 -1 10 and C= 1 -3 2 100 1 100 (a) Compute det A, det B, det C, det(AB) and det(A + B). (b) Verify that A and C are inverse matrices and use this fact to (i) solve the simultaneous equations: x – 2y + z = 2 2x – y - 2= -1 x + 2y + 2z = 3...

• ### please help!!! Use an inverse matrix to solve each system of linear equations. (a) x +... please help!!! Use an inverse matrix to solve each system of linear equations. (a) x + 2y = -1 x-2y = 3 (x, y)=( (b) x + 2y = 7 x - 2y = -1 (x, y) = Use an inverse matrix to solve each system of linear equations. (a) X1 + 2x2 + x3 = 0 X1 + 2x2 - *3 = 2 X1 - 2x2 + x3 = -4 (X1, X2, X3) - (b) X1 + 2x2 +...

• ### Use Gauss-Jordan row reduction to solve the given system of equations. HINT [See Examples 1-6.] (If...

Use Gauss-Jordan row reduction to solve the given system of equations. HINT [See Examples 1-6.] (If there is no solution, enter NO SOLUTION. If the system is dependent, express your answer in terms of x, where y = y(x) and z = z(x).) -1/2x+y-1/2z=0 -1/2x-1/2y+z=0 x-1/2y-1/2z=0 (x,y,z)=

• ### I am really stuck on these problems

I am really stuck on these problems. I've worked a lot of them but I can't get these. Sometimes I think I know the answer but I can't show how I got it. 1.) Solve each matrix equation for X.2X + 5A = B2.) Find the following matrices: a. AB b. BAA= 2 43 14 2B=3 2 0-1 -3 53.) Find A-1 by forming A|I and then using row operations to obtain I|B, where A-1 = B, check that AA-1=I...

• ### 5 1 Solve the following system of equations by using the inverse of the coefficient matrix.... 5 1 Solve the following system of equations by using the inverse of the coefficient matrix. The inverse of the coefficient matrix is shown. 0 4 4 4 11 1 Niw w 2 2 1 А x - 2y + 3z = -1 3 13 1 -2 y - Z + W = -5 4 4 4 - 3x + 3y - 22 + 5 w = -2 3 5 1 - 1 2y - 32 + W = 3...

• ### Solve the system of equations using Gaussian elimination or Gauss-Jordan elimination. 2-y + 2z = 0... Solve the system of equations using Gaussian elimination or Gauss-Jordan elimination. 2-y + 2z = 0 2 - 2y + 3z = -1 2.x – 2y+z= -3

• ### Hello, The instructions for this problem is: Use Laplace Transforms and Inverse Laplace Transforms to solve... Hello, The instructions for this problem is: Use Laplace Transforms and Inverse Laplace Transforms to solve the following three system of differential equations. x' (t) - x(t) + 2y(t) = 0 - 2 x(t) + y'(t)- y(t) = 0 x(0) = 0; y(0) 1 4

• ### #2. Solve the system of equations by any method. ( x + 2y + 3z +... #2. Solve the system of equations by any method. ( x + 2y + 3z + 4w = 5 J -5x - 4y + 3z + 2w = 1 1 x-y+z-w = 1 2x + y + 2z + w = 2 Answer: (x,y,z,w) =